A NON-LINEAR ANALYSIS OF ENERGY POVERTY, BIOMASS ENERGY CONSUMPTION AND HEALTH OUTCOMES IN DEVELOPING COUNTRIES: PANEL DATA ANALYSIS - Dr. Hina Ali; Zarish Nadeem; Dr. Hina Shafiq; Nazish Iftikhar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Energy poverty is a very main or genuine problem in developing countries. In this modern world, energy poverty is a very big issue because the majority of people live in those areas where the availability of electricity is not good. It becomes very difficult for those people who live in rural areas. The main objective of this research is to analyze the different impacts of energy access on the determinants of the health sector based on energy poverty. The role of carbon dioxide emissions on the health sector and investigate the effect of combustible renewable energy on the health sector in 82 developing countries. For analysis purpose the study use panel data for the period 1990-to 2021. Health index is used as a dependent variable while independent variables are energy poverty of the total population, energy poverty in rural population, energy poverty in urban population, carbon dioxide emission, combustible renewable and waste, industry including construction (value added), primary school enrollment, exports of goods and services and population. This study uses Panel Quantile Regression (PQR) econometric technique for estimation purpose. The results show that the health index is positively affected by energy poverty, biomass energy consumption and carbon dioxide emission. The findings tell the link between health outcomes with energy poverty, biomass energy consumption, and carbon dioxide emission. This study suggests that government should take to provide electricity in developing countries. The availability of electricity improves health outcomes.